2021
DOI: 10.1161/jaha.120.020721
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Costimulatory Molecule CD137 in Endothelial Cells

Abstract: CD137 (4‐1BB, tumor necrosis factor receptor superfamily 9) is a surface glycoprotein of the tumor necrosis factor receptor family that can be induced on a variety of immunocytes and nonimmune cells, including endothelial cells and smooth muscle cells. The importance of CD137 in immune response has been well recognized; however, the precise biological effects and underlying mechanisms of CD137 in endothelial cells are unclear. A single layer of cells called the endothelium constitutes the innermost layer of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Upregulation of CD137 in ECs leads to endothelial dysfunction, which subsequently increases the expression of adhesion molecules on ECs and pro-in ammatory cytokine production by them; both of these processes augment the recruitment and migration of leukocytes to exacerbate atherosclerotic process 7,8 . Based on the above ndings, it is conceivable that a high-dose systemic exposure of PTX upregulates mediators that are known to trigger cascades of secondary events increasing the atherothrombotic process in the vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of CD137 in ECs leads to endothelial dysfunction, which subsequently increases the expression of adhesion molecules on ECs and pro-in ammatory cytokine production by them; both of these processes augment the recruitment and migration of leukocytes to exacerbate atherosclerotic process 7,8 . Based on the above ndings, it is conceivable that a high-dose systemic exposure of PTX upregulates mediators that are known to trigger cascades of secondary events increasing the atherothrombotic process in the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…CKS2 interacts with cyclin-dependent kinases to regulate the cell cycle and is associated with atherosclerosis 6 . CD137 mediates adhesion molecules on ECs and mediates EC dysfunction and pro-in ammatory cytokine response 7,8 . MCP-1 is a well-established pro-in ammatory cytokine associated with atherothrombotic diseases 41,42 .…”
Section: Paclitaxel Compromises Fundamental Endothelial Cell Function...mentioning
confidence: 99%
“…CD137 (TNFRSF9) is expressed in a variety of immunocytes and nonimmune cells, including ECs and smooth muscle cells. CD137 is involved in several known biological functions in ECs, including inflammation, angiogenesis, and apoptosis [ 51 ]. Previous studies have shown that the expression of CD137 is upregulated in atheroma-associated vascular cells in both mouse and human atherosclerotic plaque lesions in vivo [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“… 118 There are also reports of 4–1BB expression on nonimmune cells like adipocytes 119 and atherosclerosis- or cancer-induced 4–1BB expression on blood vessel endothelial cells. 120 , 121 4–1BB agonism has both pathogenic and protective role in type 1 diabetes mouse models 122 , 123 and obesity-induced inflammations. 119 , 124 All this may play a role in the 4–1BB-mediated MoA as well as irAEs, and has to be carefully considered.…”
Section: Clinical Safety and Functionalitymentioning
confidence: 99%